PBB DI TENGAH ARUS DEMOKRATISASI - Mufid, Mufid (Jurnal Bestari, 1993)
United nation organization (UNO) is world institution consists of a great number of countries. Its existence must be considered proportionally in order to get a better image of its role. After solving ?several? world affairs, it will be challanged to solve many mondial problems. UNO consists of developed and developing countries. When the Developed countries tend to dominate and manipulate the role of its existence, it is important to consider the pillars of democracy as the best way to reach an ideal world balance.